Analisis Interaksi Senyawa Guvakolin dan Homoarekolin terhadap MAO-A secara in Silico - Riryn Novianty (LPPM Universitas Muhammadiyah Riau, 2022)
This study was aimed to conduct the inhibitory activity of the MAO-A enzyme (PDB ID: 2Z5Y) by the active compounds of Areca catechu L. The method used is in silico approach using AutoDock Vina, PyMol, and Discovery Studio (DSV). The prediction of pharmacokinetic properties and drug-likeness used the Swiss-ADME online website. The docking results exhibited guvacoline has a binding free energy value of -5.9 kcal / mol compared to homoarecoline (-5.4 kcal / mol), and positive control (-5.7 kcal / mol). Guvacoline compounds have a hydrogen bond in the active site of the enzyme. Areca nut compounds obtained good results on pharmacokinetic properties, but not so good on the BBB parameter. The compounds obtained good results for the parameters of the Lipinski, Veber rule, bioavailability score, but the guvacoline compounds could not meet Ghose's rule. The results of the bioavailability radar showed that the compounds have properties as oral drug.